Uncovering the Microbiota of Bagworm Metisa plana (Lepidoptera: Psychidae) in Oil Palm Plantations in Malaysia - Andrew Ting; Cik Mohd Rizuan Zainal Abidin; Noor Hisham Hamid; Ghows Azzam; Hasber Salim (Tropical Life Sciences Research, 2023)
Bagworm Metisa plana is one of the major pests in Malaysia’s oil palm plantation, with infestation resulting in huge economical loss. Currently, the microbial profile of the bagworm has yet to be study. Understanding the biology of the pest such as the bacterial community is crucial as bacteria associated with insects often provide benefits to the insect, giving the insect host a better chance of survival. Here, 16S amplicon sequencing was used to identify the bacteria community of M. plana. Additionally, two comparisons were made, the bacterial communities between two larval stages (early instar stage and late instar stage) from outbreak area; the bacterial communities of late instar stage larvae from non-outbreak between outbreak areas. From this study, it was found that the bacterial community of M. plana consisted of Proteobacteria, Actinobacteria, Bacterioidetes, Firmicutes and other minor phyla, with Proteobacteria being the most dominant phylum. Furthermore, bacterial genera of M. plana consisted of Pantoea, Curtobacterium, Pseudomonas, Massilia and other minor genera, with Pantoea being the most dominant. It was also found that the alpha and beta diversity in both comparisons were not significantly different. We present our data as a first insight towards the bacterial community of M. plana, paving a way towards understanding the biology of the bagworm M. plana.